Biodiversity consequences of Caulerpa prolifera takeover of a coastal lagoon - Parreira, Filipe (2021)
The genus Caulerpa has attracted much attention because many of its species were introduced into non-native regions and became notoriously invasive. This is the case of Caulerpa prolifera that has been rapidly expanding in Ria Formosa lagoon, taking over the deeper unvegetated soft bottoms and competing with seagrass meadows in the shallower areas. Here we address how C. prolifera invasion may affect the support of biodiversity, and specifically, the provision of habitat and nursery for commercial species by the native habitats of this coastal lagoon. Even though no significant differences in total species richness, diversity and evenness were found between C. prolifera and the native unvegetated habitat, the dissimilarity between these two habitats was highest, mostly driven by the extreme reduction of the gastropod Bittium reticulatum and of the tanaid Apseudopsis formosus. This may implicate changes in the trophic interactions of the ecosystem, for example decreasing the tanaid food source for seahorses, which are presently endangered in the lagoon. On the other hand, the fauna species richness, diversity and evenness were significantly higher in the native seagrass habitat than in C. prolifera. Juveniles of valuable flat and sparid fish were only observed in unvegetated sediments and seagrass meadows, respectively. The aggressive spread of C. prolifera in Ria Formosa may alter the structure of native faunal communities, with likely negative implications on fisheries. Nevertheless, the global biodiversity of the lagoon will not be likely drastically affected unless the seaweed takes over the seagrass meadows.